Trends influencing researcher education and careers: What do we know, need to know and do in looking forward? - Castelló, Montserrat; McAlpine, Lynn; Pyhalto, Kirsi (Frontline Learning Research, 2015)
Over the past twenty years, there has been a growing international focus on doctoral education. While this investment has definitely advanced our knowledge, we argue the need to expand our conceptualization of the preparation of researchers to include individuals with up to 10 years’ experience in universities and beyond. Such early career researchers (ECRs) find themselves caught up in changes brought about by national and international policies and strategies, e.g., reduced public funding of universities, changes in funding council policies, more quality assurance, etc. These issues led to the creation of EARLI SIG 24, Researcher Education and Careers, and this special issue brings together the outcome of our first scholarly discussion at the SIG 24 inaugural meeting in September 2014 in Barcelona. It consists of five co-authored papers that address multiple levels and issues of researcher education: establishing the multifaceted phenomenon researcher education and careers is and providing key concepts that others might take up, e.g., informal/invisible curriculum; the personal as a sphere of activity that may collide with the sphere of work; drivers of education that can provide cross-national points of comparison. Further, by identifying gaps in the literature, these papers together lay out an ambitious research agenda in a number of areas related to researcher education. In the process, they provide an extensive list of references well worth exploring since they represent the knowledge networks of over thirty researchers.